2019
DOI: 10.1097/jxx.0000000000000154
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent obesity in the past decade: A systematic review of genetics and determinants of food choice

Abstract: Background and purpose: As the incidence of global obesity increases, concerns about adverse health outcomes in adolescents continues to rise. The complexity and expense of this problem require early recognition and specific preventive treatments. Knowledge of genetics and determinants of food choices contributing to adolescent obesity warrants further examination. The primary goal was to appraise the literature from the past decade (2007–2017) on the current state of food choice and genetic deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
0
9
0
9
Order By: Relevance
“…These data suggest that repeated exposure to 3 consecutive non‐school days may have similar effects. Older children, such as the 8th and 11th graders surveyed here, also have increasing autonomy over food choice 21 and physical activity participation 22 compared to younger children. In this study, we showed significantly more frequent sugar sweetened beverage consumption and less frequent water consumption among 4‐ versus 5‐day week students, although other differences in food and beverage consumption were not observed.…”
Section: Discussionmentioning
confidence: 91%
“…These data suggest that repeated exposure to 3 consecutive non‐school days may have similar effects. Older children, such as the 8th and 11th graders surveyed here, also have increasing autonomy over food choice 21 and physical activity participation 22 compared to younger children. In this study, we showed significantly more frequent sugar sweetened beverage consumption and less frequent water consumption among 4‐ versus 5‐day week students, although other differences in food and beverage consumption were not observed.…”
Section: Discussionmentioning
confidence: 91%
“…Bu alanda yapılan sistematik inceleme ve meta analizler adölesanların fast food tüketme oranının çok yüksek olduğunu; bu durumun obezite ile yakından ilişkili olduğu ve fast food tüketiminde arkadaş ve sosyal medyanın önemli rolü olduğu yönünde çıkarımlar içermektedir. [30][31][32]…”
Section: Discussionunclassified
“…В то же время высокие темпы распространения ожирения за последние 30 лет в основном связаны с культурными и экологическими изменениями. Высококалорийная диета, увеличение размера порций, нарушенный суточный ритм приема пищи, малоподвижный образ жизни, хронический стресс, а также все более часто диагностируемые расстройства пищевого поведения являются основными факторами, способствующими развитию ожирения [7], т.е. наследственная предрасположенность к развитию ожирения реализуется под воздействием указанных факторов.…”
Section: этиология и патогенез заболевания или состояния (группы заболеваний или состояний)unclassified
“…• При осмотре кожных покровов рекомендуется обратить внимание на наличие стрий, участков гиперпигментации кожи, характер оволосения [7,10,14,[43][44][45].…”
Section: физикальное обследованиеunclassified